2021
DOI: 10.1186/s12711-021-00674-7
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious protein-coding variants in diverse cattle breeds of the world

Abstract: The domestication of wild animals has resulted in a reduction in effective population sizes, which can affect the deleterious mutation load of domesticated breeds. In addition, artificial selection contributes to the accumulation of deleterious mutations because of an increased rate of inbreeding among domesticated animals. Since founder population sizes and artificial selection differ between cattle breeds, their deleterious mutation load can vary. We investigated this question by using whole-genome data from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Similar results were reported by comparing the exomes of domesticated and wild yaks (Xie et al, 2018). Using 432 animals belonging to 54 worldwide cattle breeds, a previous study found a negative correlation between heterozygosity and deleterious mutational load, which suggests that breeds that have low genetic variation have higher deleterious mutational load than those with high genetic variation (Subramanian, 2021). Since heterozygosity is the product of N e and mutation rate (μ), and the mutation rate is largely similar across breeds, the above relationship implies a negative correlation between N e and the mutation load.…”
Section: Introductionsupporting
confidence: 83%
“…Similar results were reported by comparing the exomes of domesticated and wild yaks (Xie et al, 2018). Using 432 animals belonging to 54 worldwide cattle breeds, a previous study found a negative correlation between heterozygosity and deleterious mutational load, which suggests that breeds that have low genetic variation have higher deleterious mutational load than those with high genetic variation (Subramanian, 2021). Since heterozygosity is the product of N e and mutation rate (μ), and the mutation rate is largely similar across breeds, the above relationship implies a negative correlation between N e and the mutation load.…”
Section: Introductionsupporting
confidence: 83%
“…Previous studies showed that the dN/dS ratios for domesticated animals such as dog, cow, yak, pig, and silkworm and plants such as rice, soybean, and sunflower were significantly higher than those of their wild counterparts (Lu, et al 2006;Mezmouk and Ross-Ibarra 2014;Renaut and Rieseberg 2015;Kono, et al 2016;Pedersen, et al 2017;Ramu, et al 2017;Makino, et al 2018;Peischl, et al 2018;Xie, et al 2018;Bosse, et al 2019;Robinson, et al 2019;Nicolas Dussex 2021;Subramanian 2021). Furthermore, domesticated plants and animals were found to have more homozygous deleterious SNVs than their wild relatives Xie, et al 2018;Subramanian 2021).…”
Section: Discussionmentioning
confidence: 98%
“…Reduction in population size was also known to increase the frequencies of rare deleterious variants, and hence the number of homozygous SNVs is expected to be high in bottlenecked populations. Indeed, significantly higher numbers of homozygous nonsynonymous SNVs are frequently reported in small or bottlenecked populations (Marsden, et al 2016; Xie, et al 2018; Subramanian 2021). Studies of bottlenecked populations also observe an abundance of homozygous SNVs that were predicted to be deleterious based on their functional consequences or evolutionary constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Cattle is one of the most economically important livestock species, supplying humans with a substantial fraction of animal protein. Driven by the high selection intensity of economically important traits, compared to humans, cattle has a different population structure, such as smaller effective population size (Ne ~100), higher linkage disequilibrium (LD) among genomic variants, and higher inbreeding rate (i.e., resulting in the accumulation of deleterious mutations) [ 6 ]. Furthermore, millions of highly accurate phenotypic records, including fertility, health, and growth traits, have been collected for cattle [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%